Analisis Perkerasan Kaku (Rigid Pavement) pada Akses Jalan Lapangan Tembak Batalyon Armed 10 Kostrad Bogor – Jawa Barat - De Jesus , Arcelia ; Arifianto, Andy Kristafi ; Rahma, Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Access Road for Shooting Field Armed Battalion 10 Kostrad Bogor is one of the special roads or primary local roads located in the Province of West Java, which connects the Battalion Headquarters with the training ground namely the shooting range. Damage to the road structure in general climbing and decreasing the original use of flexible pavement is no longer able to withstand traffic volume and load, so to overcome this feasible pavement on this road uses rigid pavement. The data needed is CBR data and daily traffic for planning. This writing aims to get a redesign of rigid pavement planning and road reinforcement that already exists with the method used is the Portland method (Bina Marga) which is based on Pd T-14-2003. From the results of data processing obtained traffic growth (5%), Daily Traffic Plan 580 vehicles / day for 1 lane 2 directions, subgrade CBR 4.5%, effective CBR 43%. Plate thickness at 22 cm pavement, percentage of fatigue damage (0% <100%), percentage of erosion damaged (10.80% <100%), thickness of foundation pavement used 10 cm Skinny Concrete Mixture. The connection uses dowel reinforcement ? 33 mm, length 450 mm, distance 300 mm. Tie bar uses ? 16 mm, length 700 mm, distance 750 mm. Wire mesh reinforcement ? 8 mm - 150 mm.